2014
DOI: 10.1080/02757540.2014.894985
|View full text |Cite
|
Sign up to set email alerts
|

Chronic exposure effects of copper on growth, metamorphosis and thyroid gland, liver health in Chinese toad,Bufo gargarizanstadpoles

Abstract: The impact of copper exposure on Chinese toad (Bufo gargarizans) tadpoles was investigated in this study. First, the 96h LC50 value of copper was 8.697 μM, by means of a 4 d acute toxicity test. Second, we studied the chronic effects of copper on B. gargarizans tadpoles at control, 0.025, 0.1 and 1.0 μM concentration. Survival, body length, body weight, developmental stage, incidence of metamorphic climax, and size at metamorphic climax were determined. In tadpoles developed to metamorphic climax (stage G42), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…Chai et al (2014, 2017) also found proportion of Asiatic toads to reach metamorphic climax to be less sensitive than total size and size of hind limb and tail at GS 42. Although metamorphic endpoints were often more sensitive than apical endpoints (Parris and Baud 2004; Peles 2013; Wang et al 2016), there were cases where apical endpoints were as sensitive or more sensitive when comparing different GS or specific metamorphic endpoints (e.g., proportion of individuals to complete metamorphosis; Chai et al 2014).…”
Section: Comparative Sensitivity Of Different Endpointsmentioning
confidence: 95%
See 4 more Smart Citations
“…Chai et al (2014, 2017) also found proportion of Asiatic toads to reach metamorphic climax to be less sensitive than total size and size of hind limb and tail at GS 42. Although metamorphic endpoints were often more sensitive than apical endpoints (Parris and Baud 2004; Peles 2013; Wang et al 2016), there were cases where apical endpoints were as sensitive or more sensitive when comparing different GS or specific metamorphic endpoints (e.g., proportion of individuals to complete metamorphosis; Chai et al 2014).…”
Section: Comparative Sensitivity Of Different Endpointsmentioning
confidence: 95%
“…Chen et al (2007) found the growth rate (mm/d; 25 μg/L) of northern leopard frog tadpoles to be more sensitive to Cu than proportion of individuals that metamorphosed, time to metamorphic climax (GS 42), and time required for tail resorption (GS 42-46; all 100 μg/L). Chai et al (2014Chai et al ( , 2017 also found proportion of Asiatic toads to reach metamorphic climax to be less sensitive than total size and size of hind-limb and tail at Accepted Article GS 42. Although metamorphic endpoints were often more sensitive than apical endpoints (Parris and Baud 2004;Peles 2013;Wang et al 2016), there were cases where apical endpoints were as sensitive or more sensitive when comparing different GS or specific metamorphic endpoints (e.g., proportion of individuals to complete metamorphosis) (Chai et al 2014).…”
Section: Metamorphosismentioning
confidence: 99%
See 3 more Smart Citations